2016
DOI: 10.1371/journal.pone.0167749
|View full text |Cite
|
Sign up to set email alerts
|

GBA Variants Influence Motor and Non-Motor Features of Parkinson’s Disease

Abstract: The presence of mutations in glucocerebrosidase (GBA) gene is a known factor increasing the risk of developing Parkinson’s disease (PD). Mutations carriers have earlier disease onset and are more likely to develop neuropsychiatric symptoms than other sporadic PD cases. These symptoms have primarily been observed in Parkinson’s patients carrying the most common pathogenic mutations L444P and N370S. However, recent findings suggest that other variants across the gene may have a different impact on the phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
130
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(144 citation statements)
references
References 45 publications
13
130
1
Order By: Relevance
“…The finding that disease risk and clinical characteristics in PD and DLB seem dependent on GBA1 mutation severity are consistent with previous reports . We now show for both disease entities that CSF biomarker profiles of total alpha‐synuclein also seem dependent on mutation severity.…”
Section: Discussionsupporting
confidence: 92%
“…The finding that disease risk and clinical characteristics in PD and DLB seem dependent on GBA1 mutation severity are consistent with previous reports . We now show for both disease entities that CSF biomarker profiles of total alpha‐synuclein also seem dependent on mutation severity.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to cognitive decline, various other nonmotor symptoms including REM sleep behavior disorder, hyposmia, and autonomic dysfunction seem to be more frequent [14]. Interestingly, it has recently been demonstrated that also the E326K variant predicts a more rapid progression of cognitive dysfunction and motor symptoms in patients with PD [15].…”
Section: Discussionmentioning
confidence: 99%
“…GBA1 heterozygotes have an earlier age at onset compared with noncarriers of 3‐6 years for PD and 5‐7 years for DLB, respectively. Mean age at onset in heterozygous PD carriers is about 50‐55 years .…”
Section: Clinical and Neuroimaging Features Of Gba‐related Synucleinomentioning
confidence: 99%